Hubungan Tingkat Konsumsi Natrium, Kalium, dan Status Obesitas dengan Tekanan Darah Penderita Hipertensi di Puskesmas II Denpasar Utara - Ni Made Ayumi Amelia Baktika; Ni Komang Wiardani; I Wayan Juniarsana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2026)
Hypertension is known as a "Hidden Disease" because it often does not show clear symptoms. Blood pressure is said to be high if it reaches â‰¥140/90 mmHg, which is often influenced by excessive sodium consumption, low potassium, and obesity status. This study aims to analyze the relationship between sodium, potassium consumption levels, and obesity status with blood pressure in hypertension patients at Puskesmas II North Denpasar. This observational research with a cross-sectional design was conducted from February to March 2025 with 93 samples. Data on sodium and potassium consumption were collected using the form (SQ-FFQ), obesity data through measurements (BMI) then categorized, and blood pressure was measured with RGB BPM PRO (Blood Pressure Monitor). The statistical test used is the Spearman rank. Results showed (79,6%) of samples consumed excess sodium, (87,1%) lacked potassium, (52,7%) were obese, and (61,3%) have uncontrolled blood pressure.. There is a significant relationship between sodium and potassium consumption levels and blood pressure (p<0.05), but no relationship between obesity and blood pressure (p>0.05).Keywords: Sodium, potassium, obesity status, hypertension.